(untitled) (Journal of actual problems of jurisprudence, 2016)
In this article the author considers essence and value of internal belief as criterion of an assessment of the proofs, criminal trial which was the main link. The author opens process of formation of internal belief and circumstance influencing them to formation. In article as the category sense of justice is considered and need of its standard fixing is specified.